Meditative Therapy in Reducing Anxiety as a Complementary Therapy: a Trend and Knowledge on Adolescent - Kartika, Imelda Rahmayunia; Faloq, Enggia; Rezkiki, Fitrianola; Febrina, Cory (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
AbstractBackground: Complementary therapy has become an option for various diseases over the time. One kind of disease that can be given complementary intervention is anxiety. Nowadays, many young people suffer from anxiety disorders and they don't know how to deal with them properly. Make them less than optimal in achieving their life goals. The type of complementary therapy that can be used to reduce anxiety is meditation therapy. This survey aims to get an overview of the trends and knowledge of the younger generation about meditation in reducing excessive anxiety.Methods: This study uses an analytical descriptive design to see an overview of the anxiety level on adolescents and their knowledge about meditation in reducing anxiety disorders.Results: The results obtained from 129 respondents 85.3% of respondents said they had experienced excessive anxiety and as many as 63.6% of respondents said they had never done meditation.Conclusion: It can be said that the younger generation does not know about meditation and its benefits in reducing anxiety disorders. It is hoped that nurses can educate and introduce several therapies to reduce anxiety, including meditation therapy.